Almost Common Value Auctions: The "Wallet Game" and its Applications to Takeover Battles and Airwaves Auctions. - Klemperer, P (Nuffield College (University of Oxford), 1997)
We use a classroom game, the "wallet Game", to show that in standard ascending, i.e. English, auctions of close-to-common-values objects, even slight asymmetries between bidders can have very large effects on prices. Examples of small asymmetries are a small value advantage for one bidder or a small ownership of the object by one bidder; the effects of these asymmetries are greatly exarcabated by entry costs or bidding costs. We discuss applications to Airwaves Auctions and Takeover Battles including the Glaxo-Wellcome Merger.